Structural behaviour of prestressed concrete sleepers reinforced with high-performance macro synthetic fibres. (November 2022) - Camille, Christophe; Mirza, Olivia; Kirkland, Brendan; Clarke, Todd
Highlights: Structural assessment for three types of railway sleeper under static loadings; Effects of macro synthetic fibre and prestressed steel wire in reinforcing concrete sleeper; Macro synthetic fibre effectively inhibit crack propagation and increase the fracture toughness; Presents the failure mechanisms of railway sleeper at rail seat and centre cross-sections. Abstract: The application of macro synthetic fibre reinforced concrete (MSFRC) innovatively addresses the current cracking and corrosion issues associated with the prestressed concrete railway sleeper. In this paper, a structural assessment of traditional concrete sleepers reinforced with high-strength, prestressed steel and macro synthetic fibres is provided. Detailed review on the rail seat and centre sections of the railway sleeper is presented to critically evaluate the mechanical benefits and feasibility of a complete replacement of prestressed steel with macro synthetic (polypropylene) fibres. Three types of sleeper were individually subjected to both positive and negative moments at these critical sleeper sections for their performances to be compared at cracking, ultimate capacity and failure. Accordingly, the potential implementation of MSFRC in sleepers has been proposed to cost-efficiently improve the current design for the railway industry.